Competitive co-adsorption of bacteriophage MS2 and natural organic matter onto multiwalled carbon nanotubes. (1st December 2020) - Jacquin, Céline; Yu, Diya; Sander, Michael; Domagala, Kamila W.; Traber, Jacqueline; Morgenroth, Eberhard; Julian, Timothy R.
Abstract: A leading challenge in drinking water treatment is to remove small-sized viruses from the water in a simple and efficient manner. Multi-walled carbon nanotubes (MWCNT) are new generation adsorbents with previously demonstrated potential as filter media to improve virus removal. This study therefore aimed to evaluate the field applicability of MWCNT-filters for virus removal in water containing natural organic matter (NOM) as co-solute to viruses, using batch equilibrium experiments. Contrary to previous studies, our results showed with MS2 bacteriophages single-solute systems that the affinity of MWCNT for MS2 was low, since after 3 h of equilibration only 4 log10 reduction value (LRV) of MS2 (20 mL at an initial concentration of 10 6 PFU MS2/mL) were reached. Single solute experiments with Suwannee river NOM (SRNOM) performed with environmentally-relevant concentrations showed MWCNT surface saturation at initial SRNOM concentrations between 10 and 15 mgC/L, for water pH between 5.2 and 8.7. These results suggested that at NOM:virus ratios found in natural waters, the NOM would competitively suppress virus adsorption onto MWCNT, even at low NOM concentrations. We confirmed this expectation with SRNOM-MS2 co-solute experiments, which showed an exponential decrease of the MS2 LRV by MWCNT with an increase in the initial SRNOM concentration. More interestingly, we showed that pre-equilibrating MWCNT with a SRNOM solution at a concentration as low as 0.4 mgC/L resulted in a LRV decrease of 3 for MS2, due to the formation of a negatively charged SRNOM adlayer on the MWCNT surface. Complementary batch experiments with natural NOM-containing waters and competition experiments with SRNOM in the presence of CaCl2 confirmed that the presence of NOM in waters challenges virus removal by MWCNT-filters, irrespective of the concentration and type of NOM and also in the presence of Ca 2+ . We therefore conclude that MWCNT-filters produced with commercially available pristine MWCNT cannot be considered as a viable technology for drinking water virus removal. Graphical abstract: Image 1 Highlights: LRV of MS2 increase with MWCNT mass, but are little affected by solution pH. SRNOM adsorption onto MWCNT is pH dependent. SRNOM competes with MS2 for adsorption to MWCNT, even at low SRNOM concentrations. NOM suppresses MS2 adsorption, irrespective Ca2+ concentration and NOM composition. In practice, MWCNT is insufficiently selective for viruses to ensure virus removal.